An Organizational Guideline for Gynecologic Oncology Services. Issue 4 (1st May 2015) - Fung-Kee-Fung, Michael; Kennedy, Erin B.; Biagi, Jim; Colgan, Terry; D'Souza, David; Elit, Laurie M.; Hunter, Amber; Irish, Jonathan; McLeod, Robin; Rosen, Barry
Abstract : Objectives: Documented variations in practice compelled the need to establish a network that would facilitate the flow of patients through the care continuum of a provincial health care system in accordance with best practices. Therefore, a guideline was developed to provide recommendations for the optimal organization of gynecologic oncology services in this higher resource location to improve access to multidisciplinary care and appropriate treatment. Methods: A systematic review was conducted of Web sites of international guideline developers, relevant cancer agencies, and Medline and EMBASE from 1996 to 2011 using search terms related to gynecologic malignancies, combined with organization of services, patterns of care, and various facility and physician characteristics. The results of the review were combined with expert consensus and stakeholder consultation to develop a gynecologic oncology services organizational guideline. Results: The evidence review yielded a lower quality evidence base; therefore, recommendations were determined through consensus, including guidance for physician and hospital specialization, and other domains including human and physical resources. Definitive surgical treatment of most invasive cancers by subspecialist gynecologic oncologists is recommended. In addition, it is recommended that these subspecialists provide care within designated gynecologic oncology centers. The recommendations also outline which services, such as radiation therapy, may be provided in other affiliated centers. Multidisciplinary team management is also endorsed. Conclusions: These recommendations are intended to allow a collaborative community of practice, supported by formal interorganizational processes, to evolve to facilitate adherence to guidelines and best practices at a system-wide level.